The timing and consequences of seasoned equity offerings: A regression discontinuity approach - Dittmar, Amy; Duchin, Ran; Zhang, Shuran (Journal of Financial Economics, 2020)
The likelihood of seasoned equity offerings (SEOs) jumps discontinuously when the stock price equals the most recent equity offer price. Anchoring on the last offer price holds after considering executive turnovers, stock splits, earnings management, or dividend adjustments. Using a fuzzy regression discontinuity design around this cutoff, which exploits local randomness in stock prices, we investigate the consequences of anchoring in SEOs. We find significant increases in cash holdings and acquisitions of lower quality, with no real effects on investment or employment. Overall, we provide some of the cleanest estimates, to date, of the timing and causal effects of SEOs.